An Unusual Case of Heteropagus: Autosite With a Complex Cardiac Malformation - Hulya Ozkan-Ulu; Yavuz Yilmaz; Fatma Nur Sari; Nahide Altug; Nurdan Uras; Ugur Dilmen (Elsevier, 2011)
Asymmetrical form of conjoined twinning (heteropagus) is an extremely rare event with an incidence of 1-2 million live births. The incomplete component of heteropagus, namely, parasite, usually consists of rudimentary organs. Therefore, the autosite component of heteropagus can be separated successfully. A wide spectrum of associated congenital cardiac malformations, which are usually minor, has been described in autosites. However, a single-ventricle heart anomaly in the autosite has been reported in a very few cases. We report an unusual case of heteropagus with a complex cardiac malformation. To the best of our knowledge, this is the third heteropagus case in the literature with a single-ventricle heart in the autosite.